Tradisi Dakwah Kelompok Tarekat “Studi Aktivitas Dakwah Tarekat Syattariyah” - Zainal Zainal (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
Islamic preaching development dynamics in West Sumatra there was a different pattern of specific approaches, which use tradition as a means of melt strength values of Islam. Active role Sufi groups can not be separated from using tradition as a powerful media preach Islam in society. Objectivity did missionary show creativity touch his face late missionary by Sufi groups. Although impressed Islamic pattern coloring West Sumatra is Islam "Tame" or "Soft", as propagated by friendly, peaceful and enlightened Islam not as impressed Islamic Middle East "Hard" because disseminated late war. And this is also the shown missionary Apostle when staged in Medinah, not necessarily shy away from that tradition has grown. Even otherwise Until at last, slowly, across the lines of the Islamic color touch people's lives through preaching wise.